Features of the International e-Commerce Regulation in the EAEU Customs Legislation - A. S. Lebedev (Евразийская интеграция: экономика, право, политика, 2019)
Features of the international e-commerce regulation in the EAEU customs legislation are regarded in the article. The EAEU members customs authorities have a deal with the necessity of accelerated registration of the goods flow in international mail, lack of legal mechanisms to collect customs revenues and crime prevention in this area. The course on developing of the EAEU E-commerce Tax Policy Concept was proposed by Eurasian Economic Commission in 2017. The EAEU Customs Code, taking into account new trends in the world trade, entered into force in 2018. However, this is clearly not enough. The issue needs to be further analyzed both at the interstate and scientific levels.